• ## Discover

1. Home >
2. All Categories >
3. Science & Mathematics >
4. Mathematics >
5. Undecided Question
Member since:
June 17, 2012
Total points:
3 (Level 1)

## Undecided Question

Show me another »

# Solve for h: lim x->0- of ((x-h)²*(x+1))/(2(1-cos(x))=1?

i can't use L'Hopital rule or anything like that :s

h = 0

As x->0-, the denominator 2(1-cos(x)) approaches 2(1-cos(0)) = 0.
Since we are given that lim x->0- of ((x-h)²*(x+1))/(2(1-cos(x)) exists, the only way this could possibly happen is if the numerator (x-h)²*(x+1) also approaches 0 as lim x->0-.

Note that as lim x->0-, (x-h)²*(x+1) goes to (-h)²*(1) = h², so h² = 0 which gives h = 0.

Now we would like to show that, when h = 0,
lim x->0- of ((x-h)²*(x+1))/(2(1-cos(x)))=1.

lim x->0- of (x²*(x+1))/(2(1-cos(x))
= lim x->0- of x²*(x+1)(1+cos(x)) / [2(1-cos(x))(1+cos(x))]
= lim x->0- of x²*(x+1)(1+cos(x)) / [2(1-cos^2(x))]
= lim x->0- of x²*(x+1)(1+cos(x)) / (2sin^2(x))
= (1/2) [lim x->0- of (x+1)(1+cos(x))] * [lim x->0- of x² / sin^2(x)]
= (1/2) [lim x->0- of (x+1)(1+cos(x))] / [lim x->0- of (sin(x) / x)]^2
= (1/2)(0+1)(1+cos(0)) / (1^2), since sin(x) / x goes to 1 as x goes to 0
= (1/2)(1)(2)
= 1.

So h = 0 actually is a solution, and there are no other solutions for h.
The answer is precisely h = 0.

Lord bless you today!

#### None of these answers doing it for you?

Sometimes none of the answers get it just right. If so, pick "No Best Answer". Voters DO NOT get any points for voting on the No Best Answer.